Mixed Breeding of Aedes aegypti (L.) and Aedes albopictus Skuse in Four Dengue Endemic Areas in Kuala Lumpur and Selangor, Malaysia - Chen, C.D.; Nazni, W.A.; Lee, H.L.; Seleena, B.; Mohd Masri, S.; Chiang, Y.F.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2006)
Ovitrap surveillance was conducted in four dengue endemic areas in Kuala Lumpur and Selangor, Malaysia to determine the distribution and percentage of mixed breeding of both Aedes aegypti and Aedes albopictus. The percentage of mixed breeding in all study sites both indoors and outdoors accounted for 10 to 32 from the total ovitraps collected. Ae. aegypti was found at a higher frequency than Ae. albopictus in these ovitraps. This study again indicates that ovitrap is a sensitive tool to attract gravid females of more than one mosquito species to oviposit in the container.